2014
DOI: 10.1002/hipo.22384
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation‐induced increase in NMDA receptors in the hippocampus exacerbates emotional dysregulation in mice

Abstract: Epidemiological studies have shown that early life adverse events have long-term effects on the susceptibility to subsequent stress exposure in adolescence, but the precise mechanism is unclear. In the present study, mice on postnatal day 21-28 were randomly assigned to either a group or isolated cages for 8 weeks. The socially isolated (SI) mice exhibited a higher level of spontaneous locomotor activity, a longer duration of immobility in the forced swimming test (FST), significantly less prepulse inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 56 publications
4
58
0
Order By: Relevance
“…Chronic early postnatal scream sound stress upregulates NR2B levels in the CA1 and CA3, downregulates the NR2A/NR2B ratio, and impairs spatial learning and memory in male mice (Hu et al, 2016). Social isolation stress exacerbates aggressive behaviors and increases NR2A and NR2B levels in the hippocampus (Chang et al, 2015). The activation of extrasynaptic NR2B is involved in the Aβ-induced impairment of LTP in hippocampal slices (Ondrejcak et al, 2010; Li et al, 2011; Rönicke et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic early postnatal scream sound stress upregulates NR2B levels in the CA1 and CA3, downregulates the NR2A/NR2B ratio, and impairs spatial learning and memory in male mice (Hu et al, 2016). Social isolation stress exacerbates aggressive behaviors and increases NR2A and NR2B levels in the hippocampus (Chang et al, 2015). The activation of extrasynaptic NR2B is involved in the Aβ-induced impairment of LTP in hippocampal slices (Ondrejcak et al, 2010; Li et al, 2011; Rönicke et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that distinct acute or chronic stress paradigms can decrease PPI responses. This effect of stress on PPI has been described in social isolated mice [8] and Wistar [9] or female LongEvans hooded rats [10], after acute restraint stress in C57BL/6 mice [11] or repeated restraint stress in Brown Norway rats [12], and http://dx.doi.org/10.1016/j.bbr.2015.04.023 0166-4328/© 2015 Elsevier B.V. All rights reserved. after rapid eye movement sleep deprivation [13] or predator exposure [14] in male Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 80%
“…Previous studies have reported that social isolation stress is one of the major factors resulting in enhanced aggressive behavior. Social isolation led to enhanced aggressive behavior in C57BL/6j mice (Chang, Hsiao, Chen, Yu, & Gean, ; Dang et al., ; Ma, Jiang, Jiang, Wang, & Jia, ), ICR mice (Ouchi, Ono, Murakami, & Matsumoto, ; Yokota, Oshio, Moriya, & Takeda, ), ddY mice (Kawasaki et al., ; Vekovischeva, Verbitskaya, Aitta‐Aho, Sandnabba, & Korpi, ), and Swiss mice (Vekovischeva et al., ). The present findings provided evidence that 2‐week social isolation stress increased the aggressive behavior of BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%